Smart Village Synergity: Development of tourism villages as an effort to post-pandemic economic recovery - Praja, Wina Nurhayati; Azis, Abdul; Gumelar, Abih; Fuadin, Ahmad; Sudaryat, M. Ridwan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2024)
The Covid-19 pandemic has triggered an economic recession and caused major damage to the health, employment and human welfare sectors. The impact of Covid-19 that occurred in Indonesia needs to be addressed by referring to the SDGs agenda. One of them is increasing growth and development in the economic sector. Especially in developing the economic sector among the community. Therefore, researchers are trying to help economic development starting from the smallest community environment, from MSMEs in rural areas to how they can be given assistance and guidance in creating business incubators which can be done according to the capital they each have. Apart from that, it is adapted to the skills and creativity of the community in exploring various potentials that can be sold and marketed to the general public. Especially in post In the coming pandemic, of course the economic sector will experience various changes. With many aspects of the economy weakening, there are even layoffs in several sectors . The community is expected to be independent in improving the quality of its economy so that its various interests can be fulfilled properly. Therefore, the formation of a business incubator is a program that the community needs to be more focused and clear so as to help the country's economic sector at large. Thus, the aim of the service program that we are carrying out is to develop a tourist village business incubator as an effort to recover the post-pandemic economy. The service method uses an action research approach . The location of the service is in Jalatrang village, Ciamis Regency .